Racial disparities in bipolar disorder treatment and research: a call to action. (12th March 2018) - Akinhanmi, Margaret O; Biernacka, Joanna M; Strakowski, Stephen M; McElroy, Susan L; Balls Berry, Joyce E; Merikangas, Kathleen R; Assari, Shervin; McInnis, Melvin G; Schulze, Thomas G; LeBoyer, Marion; Tamminga, Carol; Patten, Christi; et al.
Abstract : Objectives: Health disparities between individuals of African and European ancestry are well documented. The disparities in bipolar disorder may be driven by racial bias superimposed on established factors contributing to misdiagnosis, including: evolving empirically based diagnostic criteria (International Classification of Diseases [ICD], Research Diagnostic Criteria [RDC] and Diagnostic and Statistical Manual [DSM]), multiple symptom domains (i.e. mania, depression and psychosis), and multimodal medical and additional psychiatric comorbidity. Methods: For this paper, we reviewed the phenomenological differences between bipolar individuals of African and European ancestry in the context of diagnostic criteria and clinical factors that may contribute to a potential racial bias. Results: Published data show that bipolar persons of African ancestry, compared with bipolar persons of non‐African ancestry, are more often misdiagnosed with a disease other than bipolar disorder (i.e. schizophrenia). Additionally, studies show that there are disparities in recruiting patients of African ancestry to participate in important genomic studies. This gap in biological research in this underrepresented minority may represent a missed opportunity to address potential racial differences in the risk and course of bipolar illness. Conclusion: A concerted effort by the research community to increase inclusion of diverse persons in studies of bipolar disorder through community engagement may facilitate fully addressing these diagnostic and treatment disparities in bipolar individuals of African ancestry.